Simple Electric Device to Isolate Nucleic Acids from Whole Blood Optimized for Point of Care Testing of Brain Damage - Bae, Mi J.; Lee, Young Mi; Choi, Ye Seul; Lee, Eunmi; Le, Minh Tan; Duc Nguyen, Thi Hong; Lee, Donghyeon; Cho, Junghwan; Han, Hyung Soo; Park, Nora Jee-Young; Chong, Gun Oh (Current Neurovascular Research, 2022)
Background: Detection or monitoring of brain damage is a clinically crucial issue. Nucleic acids in the whole blood can be used as biomarkers for brain injury. Polymerase chain reaction (PCR) which is one of the most commonly used molecular diagnostic assays requires isolated nucleic acids to initiate amplification. Currently used nucleic acid isolation procedures are complicated and require laboratory equipments. Objective: In this study, we tried to develop a simple and convenient method to isolate nucleic acids from the whole blood sample using a tiny battery-powered electric device. The quality of the isolated nucleic acids should be suitable for PCR assay without extra preparation. Methods: A plastic device with separation chamber was designed and printed with a 3D printer. Two platinum electrodes were placed on both sides and a battery was used to supply the electricity. To choose the optimal nucleic acid isolation condition, diverse lysis buffers and separation buffers were evaluated, and the duration and voltage of the electricity were tested. Western blot analysis and PCR assay were used to determine the quality of the separated nucleic acids. Results: 2ul of whole blood was applied to the cathode side of the separation chamber containing 78 ul of normal saline. When the electricity at 5 V was applied for 5 min, nucleic acids were separated from segment 1 to 3 of the separation chamber. The concentration of nucleic acids peaked around 7 8 mm from cathode side. PCR assay using the separation buffer as the template was performed successfully both in conventional and realtime PCR methods. The hemoglobin in the whole blood did not show the inhibitory effect in our separation system and it may be due to structural modification of hemoglobin during electric separation. Conclusion: Our simple electric device can separate nucleic acids from the whole blood sample by applying electricity at 5 V for 5 min. The separation buffer solution taken from the device can be used for PCR assay successfully.
Keywords: nucleic acid